Thermodynamic Properties Of In1-xBxP Semiconducting Alloys: A First-Principles Study (2014)
We have carried out first-principles total-energy calculations in order to study the electronic structure and thermodynamic properties of In 1-xBxP semiconducting alloys using the GGA and LDA formalisms within density functional theory (DFT) with a plane-wave ultrasoft pseudopotential scheme. We have also taken into account the correlation effects of the 3d-In orbitals within the LDA+U method to calculate the band-gap energy. We use special quasirandom structures to investigate the effect of the substituent concentration on structural parameter, band gap energy, mixing enthalpy and phase diagram of In1-xBxP alloys for x = 0, 0.25, 0.50, 0.75 and 1. It is found that the lattice parameters of the In 1-xBxP alloys decrease with B-concentration, showing a negative deviation from Vegard's law, while the bulk modulus increases with composition x, showing a large deviation from the linear concentration dependence (LCD). The calculated band structure presents a similar behavior for any B-composition using LDA, PBE or LDA+U approach. Our results predict that the band-gap shows a x-dependent nonlinear behavior. Calculated band gaps also shows a transition from (Γ→Γ)-direct to (Γ→Δ)- indirect at x = 0.611 and 0.566 for LDA and PBE functionals, respectively. Our calculations predict that the In1-xBxP alloy to be stable at unusual high temperature for both LDA and PBE potentials. © 2014 Elsevier B.V. All rights reserved.